The effect of social relationships on survival in elderly residents of a Southern European community: a cohort study - Rodriguez-Laso, Angel (BioMed Central, 2007)
BACKGROUND: Comparative evidence regarding the effects of social relationships on mortality in Mediterranean communities will increase our knowledge of their strengths and the ways in which they influence longevity across cultures. Men and women may benefit differently from social relationships because of cultural differences in gender roles. Psychosocial mechanisms such as social support, which may explain the effects of social networks, may also vary by culture. METHODS: Detailed information on the social relationships of a representative sample of 1,174 community-dwelling older adults was collected in Leganés, a city in central Spain. Mortality over a 6-year follow-up period was ascertained. Information on socio-demographic, health and disability variables was also collected. Cox proportional hazards models were fitted separately for men and women and for the combined sample. RESULTS: Having a confidant was associated with a 25% (95% CI 5–40%) reduction in the mortality risk. The hazard ratio for lack of social participation was 1.5 (95% CI 1.3–1.7). Being engaged in meaningful roles protected against mortality, while receipt of emotional support did not affect survival. These results were comparable for men and women. Having contact with all family ties was associated with reduced mortality only in men. Structural aspects of social networks make a unique contribution to survival, independently of emotional support and the role played in the lives of significant others. CONCLUSION: In this elderly Southern European population, the beneficial effects of social networks, social participation, engagement in the life of significant others and having a confidant call for public policies that foster intergenerational and community exchanges.